Ventriculo-peritoneal shunting devices for hydrocephalus - Garegnani, Luis (2020)
Background: Hydrocephalus is a common neurological disorder, caused by a progressive accumulation of cerebrospinal fluid (CSF) within the intracranial space that can lead to increased intracranial pressure, enlargement of the ventricles (ventriculomegaly) and, consequently, to brain damage. Ventriculo-peritoneal shunt systems are the mainstay therapy for this condition, however there are different types of shunt systems. Objectives: To compare the effectiveness and adverse effects of conventional and complex shunt devices for CSF diversion in people with hydrocephalus. Search methods: We searched the Cochrane Central Register of Controlled Trials (2020 Issue 2); Ovid MEDLINE (1946 to February 2020); Embase (Elsevier) (1974 to February 2020); Latin American and Caribbean Health Science Information Database (LILACS) (1980 to February 2020); ClinicalTrials.gov; and World Health Organization International Clinical Trials Registry Platform. Selection criteria: We selected randomised controlled trials or quasi-randomised trials of different types of ventriculo-peritoneal shunting devices for people with hydrocephalus. Primary outcomes included: treatment failure, adverse events and mortality. Data collection and analysis: Two review authors screened studies for selection, assessed risk of bias and extracted data. Due to the scarcity of data, we performed a Synthesis Without Meta-analysis (SWiM) incorporating GRADE for the quality of the evidence. Main results: We included six studies with 962 participants assessing the effects of standard valves compared to anti-syphon valves, other types of standard valves, self-adjusting CSF flow-regulating valves and external differential programmable pressure valves. All included studies started in a hospital setting and offered ambulatory follow-up. Most studies were conducted in infants or children with hydrocephalus from diverse causes. The certainty of the evidence for most comparisons was low to very low. 1. Standard valve versus anti-syphon valve. Three studies with 296 randomised participants were included under this comparison. We are uncertain about the incidence of treatment failure in participants with standard valve and anti-syphon valves (very low certainty of the evidence). The incidence of adverse events may be similar in those with standard valves (range 0 to 1.9%) and anti-syphon valves (range 0 to 2.9%) (low certainty of the evidence). Mortality may be similar in those with standard valves (0%) and anti-syphon valves (0.9%) (RD 0.01%, 95% CI -0.02% to 0.03%, low certainty of the evidence). Ventricular size and head circumference may be similar in those with standard valves and anti-syphon valves (low certainty of the evidence). None of the included studies reported the quality of life of participants. 2. Comparison between different types of standard valves. Two studies with 174 randomised participants were included under this comparison. We are uncertain about the incidence of treatment failure in participants with different types of standard valves (early postoperative period: RR 0.41, 95% CI 0.13 to 1.27; at 12 months follow-up: RR 1.17, 95% CI 0.72 to 1.92, very low certainty of the evidence). None of the included studies reported adverse events beyond those included under "treatment failure". We are uncertain about the effects of different types of standard valves on mortality (range 2% to 17%, very low certainty of the evidence). The included studies did not report the effects of these interventions on quality of life, ventricular size reduction or head circumference. 3. Standard valve versus self-adjusting CSF flow-regulating valve. One study with 229 randomised participants addressed this comparison. The incidence of treatment failure may be similar in those with standard valves (42.98%) and self-adjusting CSF flow-regulating valves (39.13%) (low certainty of the evidence). The incidence of adverse events may be similar in those with standard valves (range 0 to 1.9%) and those with self-adjusting CSF flow-regulating valves (range 0 to 7.2%) (low certainty of the evidence). The included study reported no deaths in either group in the postoperative period. Beyond the early postoperative period, the authors stated that nine patients died (no disaggregated data by each type of intervention was available, low certainty of the evidence). The included studies did not report the effects of these interventions on quality of life, ventricular size reduction or head circumference. 4. External differential programmable pressure valve versus non-programmable valve. One study with 377 randomised participants addressed this comparison. The incidence of treatment failure may be similar in those with programmable valves (52%) and non-programmable valves (52%) (RR 1.02, 95% CI 0.84 to 1.24, low certainty of the evidence). The incidence of adverse events may be similar in those with programmable valves (6.19%) and non-programmable valves (6.01%) (RR 0.97, 95% CI 0.44 to 2.15, low certainty of the evidence). The included study did not report the effect of these interventions on mortality, quality of life or head circumference. Ventricular size reduction may be similar in those with programmable valves and non-programmable valves (low certainty of the evidence). Authors' conclusions: Standard shunt valves for hydrocephalus compared to anti-syphon or self-adjusting CSF flow-regulating valves may cause little to no difference on the main outcomes of this review, however we are very uncertain due to the low to very low certainty of evidence. Similarly, different types of standard valves and external differential programmable pressure valves versus non-programmable valves may be associated with similar outcomes. Nevertheless, this review did not include valves with the latest technology, for which we need high-quality randomised controlled trials focusing on patient-important outcomes including costs.